Naturally Occurring Asbestos: Potential for Human Exposure, Southern Nevada, USA. Issue 6 (14th October 2013) - Buck, Brenda J.; Goossens, Dirk; Metcalf, Rodney V.; McLaurin, Brett; Ren, Minghua; Freudenberger, Frederick
Abstract : Amphibole asbestos minerals are known human carcinogens, and many regulations have been developed to limit occupational exposure. These minerals can also occur in the natural environment, where they may be more difficult to control. We applied a diverse set of analytical methods including scanning electron microscopy/energy dispersive spectroscopy, electron probe analysis, x‐ray diffraction, and field‐emission scanning electron microscopy to rock, soil, and dust samples and to particles attached to clothing samples and cars. We found naturally occurring fibrous actinolite, a regulated amphibole asbestos mineral, in rock, soil, and dust that can be transported by wind, water, cars, or on clothing after outdoor recreational activities. Sources of these fibrous amphiboles are several plutons in southern Nevada and Arizona and alluvial fans emanating from asbestos‐containing bedrock. The morphology of the amphibole fibers is similar to amphibole fibers found in the USEPA Superfund site at Libby, MT. We found that the morphometry of the fibrous particles in the study area did not substantially change when the original bedrock weathered into soil, and particles were eroded and transported through wind and/or water and finally settled and accumulated on natural or other surfaces. Because large populations in Boulder City, Henderson, and Las Vegas are located only a few kilometers, sometimes even only a few tens of meters, downwind from the sources, and because most of the particles are transported in suspension after they are emitted, potentially large populations in Boulder City, Henderson, and perhaps Las Vegas could be exposed. This study demonstrates a potential public health risk to several large population areas.